ZSM-5 molecular sieve with surface defects as well as preparation method and application of ZSM-5 molecular sieve

By using an excessive aluminum source to fill the defects and elute in the synthesis of ZSM-5 molecular sieve, the surface defect ZSM-5 molecular sieve with special pore structure is formed, which solves the problem of the microporous structure limiting reactant diffusion and improves the light hydrocarbon cracking reaction Conversion rate and selectivity.

CN119320147APending Publication Date: 2025-01-17SHANDONG CHAMBROAD PETROCHEMICALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411502451.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The microporous structure of ZSM-5 molecular sieve limits the diffusion of larger reactant molecules, resulting in secondary reactions and catalyst deactivation, affecting its performance in light hydrocarbon cracking reactions.

Method used

ZSM-5 molecular sieve was synthesized at a lower alkalinity using an excessive aluminum source. By filling the defects and eluting under ion exchange conditions, a surface defective ZSM-5 molecular sieve with a special pore structure was formed as a catalyst for light hydrocarbon cracking reaction.

Benefits of technology

It improves the diffusion rate of macromolecular reaction substrates in molecular sieve, enhances the reaction conversion and selectivity, reduces coke generation, and is especially suitable for light hydrocarbon cracking and yielding dienes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides a ZSM-5 molecular sieve with surface defects as well as a preparation method and application of the ZSM-5 molecular sieve. The method comprises the following steps: mixing and reacting an aluminum source, a silicon source, an alkaline substance and a template agent in a solvent to obtain gel; and carrying out crystallization, first calcination, ion exchange and second calcination on the gel to obtain the ZSM-5 molecular sieve with surface defects, when the silicon-aluminum ratio of the ZSM-5 molecular sieve is n: 1, the molar ratio of the silicon source to the aluminum source is n: (2-5). According to the method, an excessive aluminum source is adopted and serves as an aluminum source and a defect filling agent at the same time under the low alkalinity, in the preparation process, the excessive aluminum source which cannot be dissolved fills the defects in the synthesis process of the molecular sieve and is eluted under the subsequent ion exchange condition, and therefore the ZSM-5 molecular sieve with the special defect morphology is generated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of molecular sieve preparation, and in particular relates to a ZSM-5 molecular sieve with surface defects and a preparation method and application thereof. Background Art

[0002] Molecular sieves have unique skeleton structures, pore structures and adjustable acid sites, and are widely used in catalysis, adsorption, ion exchange and other fields. Among them, the ZSM-5 molecular sieve with MFI topology is composed of two intersecting 10-membered ring channels (the b axis is a straight channel and the a axis is a sinusoidal channel). Its unique pore size is in the range of 0.5~0.6 nm and is used in petrochemicals and refining. However, the individual micropores (2 nm) of the ZSM-5 molecular sieve limit the diffusion of larger reactant molecules in the molecular sieve, resulting in secondary reactions, coke formation, and even catalyst deactivation.

[0003] Studies have shown that the diffusion rate of molecules in the pore system of molecular sieves can be controlled by adjusting the axial length, porosity, and surface defects of the molecular sieve crystals, which has an important influence on the adsorption and catalytic properties of the molecular sieve. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a ZSM-5 molecular sieve with surface defects and a preparation method and application thereof. The ZSM-5 molecular sieve with surface defects has a special pore structure and has good application prospects in light hydrocarbon cracking reactions.

[0005] To achieve this object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing a surface-defective ZSM-5 molecular sieve, comprising the following steps:

[0007] S1: mixing an aluminum source, a silicon source, an alkaline substance, and a template agent in a solvent and reacting them to obtain a gel;

[0008] S2: After crystallization, first calcination, ion exchange and second calcination of the gel, a ZSM-5 molecular sieve with surface defects is obtained;

[0009] The silicon-aluminum ratio of the ZSM-5 molecular sieve is n:1, with SiO 2 、Al in aluminum source 2 O 3 According to calculation, the molar ratio of the silicon source to the aluminum source is m:1;

[0010] The n is any integer between 20 and 60, and the m is any integer between 10 and 30.

[0011] Preferably, the aluminum source is selected from aluminum hydroxide.

[0012] Preferably, the silicon source is selected from any one or more of silica gel, tetraethyl orthosilicate or silica sol.

[0013] Preferably, the alkaline substance comprises an organic base and / or an inorganic base.

[0014] Preferably, the solvent is selected from any one or more of water, ethanol or ethyl acetate.

[0015] Preferably, the template is selected from any one or more of tetrapropylammonium hydroxide, n-butylamine or tetrapropylammonium bromide.

[0016] Preferably, the molar ratio of the silicon source, aluminum source, template, solvent and alkaline substance is 1:(0.0332~0.1):(0.1~0.5):(12~30):(0.05~0.15).

[0017] Preferably, the crystallization temperature is 120-180° C. and the time is 10-72 h.

[0018] Preferably, the temperature of the first calcination and the second calcination are each independently 450-700° C., and the time is each independently 3-6 h.

[0019] Preferably, the ion exchange reagent is an acidic solution.

[0020] Preferably, the acidic solution comprises a 0.1-1 mol / L hydrochloric acid solution.

[0021] Preferably, the molar ratio of the product after the first calcination to the acidic solution is 1:(2-5).

[0022] Preferably, the ion exchange temperature is 60-80° C. and the time is 2-4 h.

[0023] In a second aspect, the present invention provides a ZSM-5 molecular sieve with surface defects prepared by the above preparation method.

[0024] In a third aspect, the present invention provides a catalyst for catalytic cracking, which comprises, by weight, 20 to 40 parts of kaolin; 30 to 50 parts of active components; 10 to 30 parts of a binder;

[0025] The active component is the ZSM-5 molecular sieve with surface defects involved in the above technical solution.

[0026] Preferably, the binder is selected from any one or more of alumina sol, silica sol, acidified pseudo-boehmite, water glass or aluminum phosphate.

[0027] Preferably, the raw material for catalytic cracking is selected from any one or more of C5~C8 alkanes, C5~C8 olefins or C6~C8 aromatics.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The present invention provides a method for preparing a ZSM-5 molecular sieve with surface defects. The method uses an excess aluminum source as both an aluminum source and a defect filler at a relatively low alkalinity. During the preparation process, the excess aluminum source that cannot be dissolved fills the defects during the synthesis of the molecular sieve and is eluted under subsequent ion exchange conditions, thereby producing a ZSM-5 molecular sieve with a special defect morphology.

[0030] The present invention adopts a one-pot method to prepare a ZSM-5 molecular sieve with surface defects, and uses it as an active component of a light hydrocarbon cracking reaction catalyst, which can increase the diffusion rate of macromolecular reaction substrates in the molecular sieve, thereby increasing the reaction conversion rate. In addition, by increasing the diffusion rate of product molecules, the occurrence of secondary reactions is reduced, the product selectivity is effectively improved, and the generation of coke is inhibited, which is very beneficial to the light hydrocarbon cracking reaction to produce more dienes. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a SEM image of the molecular sieve obtained in Example 1;

[0032] Figure 2 This is the SEM image of the molecular sieve obtained in Comparative Example 1;

[0033] Figure 3 The X-ray diffraction spectra of the molecular sieves obtained in Example 1 and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0034] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] The present invention provides a ZSM-5 molecular sieve with surface defects, which comprises the following steps:

[0036] S1: mixing an aluminum source, a silicon source, an alkaline substance, and a template agent in a solvent and reacting them to obtain a gel;

[0037] S2: After the gel is crystallized, first calcined, ion exchanged and second calcined, a ZSM-5 molecular sieve with surface defects is obtained.

[0038] In the present invention, firstly, an aluminum source, a silicon source, an alkaline substance, and a template are mixed and reacted in a solvent to obtain a gel. Among them, the aluminum source is preferably aluminum hydroxide; the silicon source is selected from any one or more of silica gel, tetraethyl orthosilicate or silica sol; the alkaline substance includes an organic base and / or an inorganic base; the solvent is selected from water; the template is selected from any one or more of tetrapropylammonium hydroxide, n-butylamine or tetrapropylammonium bromide; the solvent is selected from any one or more of water, ethanol or ethyl acetate. The present invention has no particular restrictions on the sources of the above-mentioned aluminum source, silicon source, alkaline substance, template and solvent, and they can be general commercial products.

[0039] In some embodiments of the present invention, the aluminum source, the template and the solvent are preferably mixed and stirred uniformly to obtain solution A; an alkaline substance is added to solution A to obtain solution B; and a silicon source is added to solution B to obtain a gel.

[0040] It should be noted that in the present invention, the amount of the aluminum source is excessive. That is, based on the silicon-aluminum ratio of the ZSM-5 molecular sieve being n:1, the SiO 2 、Al in aluminum source 2 O 3 According to calculation, the molar ratio of the silicon source to the aluminum source is m:1; the n can be any integer from 20 to 60 according to the commonly used values ​​of those skilled in the art, such as 20, 30, 40, 50 or 60; the m can be any integer from 10 to 30, such as 10, 15, 20, 25 or 30. The present invention uses an excess aluminum source because the excess aluminum source that cannot be dissolved at a lower alkalinity will fill the defects during the synthesis of the molecular sieve and be eluted under the subsequent ion exchange conditions, thereby producing a ZSM-5 molecular sieve with a special defect morphology.

[0041] In the present invention, since the silicon source and aluminum source, as well as the template, solvent and alkaline substance, all participate in the synthesis of gel C, they need to be considered as a whole. 2 、Al in aluminum source 2 O 3According to calculation, the molar ratio of the silicon source, aluminum source, template, solvent, and alkaline substance is 1: (0.0332~0.1): (0.1~0.5): (12~30): (0.05~0.15), preferably 1: (0.035~0.09): (0.15~0.4): (15~25): (0.08~0.12). After obtaining the gel, it is crystallized according to the present invention. In some embodiments of the present invention, the gel is preferably transferred to a reactor and crystallized for a certain time at a certain temperature. The crystallization temperature is 120~180°C, preferably 130~160°C; the time is 10~72 h, preferably 15~48 h.

[0042] After the crystallization process is completed, the first calcination process can be performed.

[0043] In some preferred embodiments of the present invention, after the crystallization treatment is completed, the obtained product is first washed and dried, and then subjected to a first calcination treatment. The washing is preferably carried out in deionized water, and the molar ratio of the product obtained by the crystallization treatment to deionized water is 1:(10-20), preferably 1:(12-15); the drying temperature is 60-120°C, preferably 80-100°C; and the drying time is 6-24 h, preferably 8-12 h.

[0044] In the present invention, the temperature of the first calcination is 450-700°C, preferably 500-600°C, and the time is 3-6 hours, preferably 4-5 hours. The purpose of the first calcination is to remove the template in the molecular sieve.

[0045] After the first calcination, the obtained product is subjected to ion exchange. The reagent for the ion exchange is an acidic solution, preferably a 0.1~1 mol / L hydrochloric acid solution. In this step, the presence of the acidic solution can elute the aluminum source (i.e., aluminum hydroxide) that fills the defects of the molecular sieve, so that the surface of the prepared molecular sieve has defects of special morphology, and the presence of defects increases the specific surface area of ​​the molecular sieve. When it is used as a catalyst, the diffusion rate of the reaction substrate and product molecules on the defective molecular sieve is accelerated, which can improve the conversion rate of the reaction, reduce the secondary reaction of the product molecules, and improve the selectivity of the reaction. In some embodiments of the present invention, the molar ratio of the product after the first calcination to the acidic solution is 1: (2~5), preferably 1: (3~4). The temperature of the ion exchange is 60~80°C, preferably 65~75°C; the time is 2~4 h, preferably 2.5~3.5 h.

[0046] After the ion exchange, according to the present invention, a second calcination is performed, the purpose of which is to remove excess chloride ions. In the present invention, the temperature of the second calcination is 450-700°C, preferably 500-600°C; the time is 3-6 hours, preferably 4-5 hours.

[0047] The invention adopts a one-pot method to prepare a ZSM-5 molecular sieve with surface defects, has simple steps, is easy to implement, and is conducive to industrialization or industrial production.

[0048] The present invention also provides a ZSM-5 molecular sieve with surface defects prepared according to the above preparation method. SEM characterization shows that the surface of the ZSM-5 molecular sieve prepared by the present invention does have defects of special morphology, such as Figure 1 shown.

[0049] The ZSM-5 molecular sieve with surface defects prepared by the present invention has a special pore structure. The molecular sieve is used as an active component in a light hydrocarbon cracking catalyst and is expected to exhibit excellent diene selectivity in the light hydrocarbon cracking reaction.

[0050] Based on this, the present invention also provides a catalyst for catalytic cracking of light hydrocarbons, which comprises 20-40 parts of kaolin, 30-50 parts of active components, and 10-30 parts of binders, preferably 30-40 parts of kaolin, 40-50 parts of active components, and 15-25 parts of binders, wherein the active component is a ZSM-5 molecular sieve with surface defects, and the binder is selected from any one or more of aluminum sol, silica sol, acidified pseudo-boehmite, water glass, or aluminum phosphate.

[0051] In the present invention, the light hydrocarbons are selected from any one or more of C5-C8 alkanes, C5-C8 olefins or C6-C8 aromatics.

[0052] The light hydrocarbon catalytic cracking catalyst prepared by the invention can improve the diffusion rate of reaction substrates, the reaction conversion rate and the diene selectivity, and is particularly suitable for the field of producing more dienes by cracking light hydrocarbons in refineries.

[0053] In order to further illustrate the present invention, the following examples are provided for detailed description. The experimental raw materials used in the following examples of the present invention are all common commercially available products.

[0054] Example 1

[0055] (1) 0.0332 mol of aluminum hydroxide, 0.1 mol of tetrapropylammonium hydroxide and 15 mol of water are mixed and stirred to obtain a solution A;

[0056] (2) adding 0.05 mol sodium hydroxide to solution A to obtain solution B;

[0057] (3) Add 4 mol of 40% silica sol to solution B to obtain gel C;

[0058] (4) Transfer gel C to a reactor and crystallize at 160 °C for 48 h;

[0059] (5) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 7 h, and calcined at 550°C for 4 h to obtain solid a;

[0060] (6) using a 0.1 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:2 to perform ion exchange on solid a, and then calcining at 550°C for 4 h to obtain solid b;

[0061] (7) Taking solid b as the catalyst active component, 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of molecular sieve, and 130 g of silica sol are added in the order of mixing and stirring to form a slurry, and the slurry is ball-milled and then spray-formed in a spray dryer;

[0062] (8) The prepared microsphere particles were calcined at 500 °C for 2 h, and the obtained samples were evaluated using a fixed fluidized bed reactor.

[0063] Example 2

[0064] (1) 0.04 mol of aluminum hydroxide, 0.2 mol of tetrapropylammonium hydroxide and 15 mol of water are mixed and stirred to obtain a solution A;

[0065] (2) adding 0.06 mol sodium hydroxide to solution A to obtain solution B;

[0066] (3) Add 4 mol of 40% silica sol to solution B to obtain gel C;

[0067] (4) Transfer gel C to a reactor and crystallize at 160 °C for 48 h;

[0068] (5) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 7 h, and calcined at 550°C for 4 h to obtain solid a;

[0069] (6) using a 0.1 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:2 to perform ion exchange on solid a, and then calcining at 550°C for 4 h to obtain solid b;

[0070] (7) Taking solid b as the catalyst active component, 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of molecular sieve, and 130 g of silica sol are added in the order of mixing and stirring to form a slurry, and the slurry is ball-milled and then spray-formed in a spray dryer;

[0071] (8) The prepared microspheres were calcined at 500 °C for 2 h, and the obtained samples were evaluated using a fixed fluidized bed reactor.

[0072] Example 3

[0073] (1) 0.05 mol of aluminum hydroxide, 0.3 mol of tetrapropylammonium hydroxide and 15 mol of water are mixed and stirred to obtain a solution A;

[0074] (2) adding 0.075 mol of sodium hydroxide to solution A to obtain solution B;

[0075] (3) Add 4 mol of 40% silica sol to solution B to obtain gel C;

[0076] (4) Transfer gel C to a reactor and crystallize at 160 °C for 48 h;

[0077] (5) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 7 h, and calcined at 550°C for 4 h to obtain solid a;

[0078] (6) using a 0.1 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:3, ion exchange was performed on solid a, and then calcined at 550° C. for 4 h to obtain solid b;

[0079] (7) Taking solid b as the catalyst active component, 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of molecular sieve, and 130 g of silica sol are added in the order of mixing and stirring to form a slurry, and the slurry is ball-milled and then spray-formed in a spray dryer;

[0080] (8) The prepared microspheres were calcined at 500 °C for 2 h, and the obtained samples were evaluated using a fixed fluidized bed reactor.

[0081] Example 4

[0082] (1) 0.0667 mol of aluminum hydroxide, 0.4 mol of tetrapropylammonium hydroxide and 15 mol of water were mixed and stirred to obtain a solution A;

[0083] (2) adding 0.1 mol sodium hydroxide to solution A to obtain solution B;

[0084] (3) Add 4 mol of 40% silica sol to solution B to obtain gel C;

[0085] (4) Transfer gel C to a reactor and crystallize at 160 °C for 48 h;

[0086] (5) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 7 h, and calcined at 550°C for 4 h to obtain solid a;

[0087] (6) using a 0.1 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:4, ion-exchanging the solid a, and then calcining at 550° C. for 4 h to obtain a solid b;

[0088] (7) Taking solid b as the catalyst active component, 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of molecular sieve, and 130 g of silica sol are added in the order of mixing and stirring to form a slurry, and the slurry is ball-milled and then spray-formed in a spray dryer;

[0089] (8) The prepared microspheres were calcined at 500 °C for 2 h, and the obtained samples were evaluated using a fixed fluidized bed reactor.

[0090] Example 5

[0091] (1) 0.1 mol of aluminum hydroxide, 0.5 mol of tetrapropylammonium hydroxide and 15 mol of water are mixed and stirred to obtain a solution A;

[0092] (2) adding 0.15 mol sodium hydroxide to solution A to obtain solution B;

[0093] (3) Add 4 mol of 40% silica sol to solution B to obtain gel C;

[0094] (4) Transfer gel C to a reactor and crystallize at 160 °C for 48 h;

[0095] (5) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 7 h, and calcined at 550°C for 4 h to obtain solid a;

[0096] (6) using a 0.1 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:5 to perform ion exchange on solid a, and then calcining at 550° C. for 4 h to obtain solid b;

[0097] (7) Taking solid b as the catalyst active component, 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of molecular sieve, and 130 g of silica sol are added in the order of mixing and stirring to form a slurry, and the slurry is ball-milled and then spray-formed in a spray dryer;

[0098] (8) The prepared microspheres were calcined at 500 °C for 2 h, and the obtained samples were evaluated using a fixed fluidized bed reactor.

[0099] Example 6

[0100] (1) 0.0332 mol of aluminum hydroxide, 0.5 mol of n-butylamine and 30 mol of water were mixed and stirred to obtain solution A;

[0101] (2) adding 0.05 mol of sodium hydroxide to solution A to obtain solution B;

[0102] (3) Add 4 mol of silica gel to solution B to obtain gel C;

[0103] (4) Transfer gel C to a reactor and crystallize at 180 °C for 10 h;

[0104] (5) washing the crystallized molecular sieve with deionized water until neutral, drying at 60° C. for 24 h, and calcining at 700° C. for 3 h to obtain solid a;

[0105] (6) using a 0.1 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:4 to perform ion exchange on solid a, and then calcining at 700°C for 3 h to obtain solid b;

[0106] (7) Taking solid b as the catalyst active component, 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of molecular sieve, and 130 g of silica sol are added in the order of mixing and stirring to form a slurry, and the slurry is ball-milled and then spray-formed in a spray dryer;

[0107] (8) The prepared microspheres were calcined at 500 °C for 2 h, and the obtained samples were evaluated using a fixed fluidized bed reactor.

[0108] Example 7

[0109] (1) 0.0332 mol of aluminum hydroxide, 0.5 mol of tetrapropylammonium bromide and 12 mol of water are mixed and stirred to obtain a solution A;

[0110] (2) adding 0.05 mol potassium hydroxide to solution A to obtain solution B;

[0111] (3) Add 4 mol of tetraethyl orthosilicate to solution B to obtain gel C;

[0112] (4) Transfer gel C to a reactor and crystallize at 120 °C for 72 h;

[0113] (5) washing the crystallized molecular sieve with deionized water until neutral, drying at 120° C. for 6 h, and calcining at 450° C. for 6 h to obtain solid a;

[0114] (6) using a 0.1 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:4, ion-exchanging the solid a, and then calcining at 450° C. for 6 h to obtain a solid b;

[0115] (7) Taking solid b as the catalyst active component, 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of molecular sieve, and 130 g of silica sol are added in the order of mixing and stirring to form a slurry, and the slurry is ball-milled and then spray-formed in a spray dryer;

[0116] (8) The prepared microsphere particles were calcined at 500 °C for 2 h, and the obtained samples were evaluated using a fixed fluidized bed reactor.

[0117] Comparative Example 1

[0118] (1) 0.0333 mol of sodium aluminate (calculated as alumina, the alumina content is 45%), 0.1 mol of tetrapropylammonium hydroxide and 15 mol of water are mixed and stirred to obtain a solution A;

[0119] (2) adding 0.05 mol sodium hydroxide to solution A to obtain solution B;

[0120] (3) Add 4 mol of 40% silica sol to solution B to obtain gel C;

[0121] (4) Transfer gel C to a reactor and crystallize at 160 °C for 48 h;

[0122] (5) The crystallized molecular sieve was washed with deionized water until neutral, dried at 60°C for 7 h, and calcined at 550°C for 4 h to obtain solid a;

[0123] (6) using a 0.1 mol / L hydrochloric acid solution at a solid-liquid ratio of 1:4, ion-exchanging the solid a, and then calcining at 550° C. for 4 h to obtain a solid b;

[0124] (7) Taking solid b as the catalyst active component, 600 g of kaolin, 130 g of aluminum sol, 70 g of phosphoric acid, 400 g of molecular sieve, and 130 g of silica sol are added in the order of mixing and stirring to form a slurry, and the slurry is ball-milled and then spray-formed in a spray dryer;

[0125] (8) The prepared microspheres were calcined at 500 °C for 2 h, and the obtained samples were evaluated using a fixed fluidized bed reactor.

[0126] Surface area and pore volume test of molecular sieve (i.e., solid b)

[0127] The test results are shown in Table 1 below:

[0128] Table 1

[0129]

[0130] It can be seen from Table 1 that the specific surface area of ​​the ZSM-5 molecular sieves with surface defects prepared in Examples 1 to 7 is significantly higher than that of the defect-free ZSM-5 molecular sieve prepared in Comparative Example 1, which is conducive to the rapid contact of the reaction substrate with the acidic site and the rapid separation of the product, thereby improving the reaction conversion rate and reducing secondary reactions.

[0131] Catalytic performance test

[0132] Catalytic evaluation test of fixed fluidized bed reactor

[0133] The test method is as follows:

[0134] Prepare 200 g of catalyst and add it to the fixed fluidized bed reactor, set the system temperature to 630 ° C, the nitrogen flow rate to 200 mL / min, and the water flow rate to 6 g / min. After nitrogen fluidization and heating, the oil pump refluxes for 1 min, 20 g of oil is fed, the reaction is 8 min, stripping is 20 min, and then the temperature is raised to 750 ° C, regenerated for 120 min, and the regeneration is completed.

[0135] After the reaction is finished, record the amount of water, oil and gas inflow, take refinery gas for analysis and collect liquid products.

[0136] The physical properties of the crude oil are shown in Table 2:

[0137] Table 2

[0138]

[0139] The test results are shown in Table 3:

[0140] Table 3

[0141]

[0142] It can be seen from Table 3 that, compared with Comparative Example 1, the diene yields of the molecular sieves with surface defects obtained in Examples 1-7 are all higher than those in Comparative Example 1. This is because the presence of surface defects increases the specific surface area of ​​the molecular sieve, accelerates the diffusion rate of the reaction substrate and product molecules on the defective molecular sieve, improves the reaction conversion rate, reduces the secondary reaction of the product molecules, reduces the generation of dry gas and coke, and improves the diene selectivity of the reaction.

[0143] In addition, in Examples 1 to 5, as the amount of aluminum source and alkali introduced increases, the silicon-aluminum ratio of the prepared molecular sieve gradually decreases, which increases the number of acid sites of the molecular sieve, is beneficial to the improvement of the reaction conversion rate, and improves the diene selectivity. Therefore, within a certain range, reducing the silicon-aluminum ratio of the synthesized ZSM-5 molecular sieve with surface defects is also beneficial to the light hydrocarbon cracking reaction to produce more dienes.

[0144] The above description of the disclosed embodiments enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A surface defective ZSM-5 molecular sieve, characterized in that: The following steps are involved: S1: mixing an aluminum source, a silicon source, an alkaline substance, and a template in a solvent and reacting them to obtain a gel; S2: After crystallization, first calcination, ion exchange and second calcination of the gel, a ZSM-5 molecular sieve with surface defects is obtained; The silicon-aluminum ratio of the ZSM-5 molecular sieve is n:1, and the molar ratio of the silicon source and the aluminum source is m:1, calculated based on SiO2 in the silicon source and Al2O3 in the aluminum source; The n is any integer between 20 and 60, and the m is any integer between 10 and 30.

2. The preparation method according to claim 1, characterized in that: The aluminum source is selected from aluminum hydroxide; The silicon source is selected from any one or more of silica gel, tetraethyl orthosilicate or silica sol; The alkaline substance includes organic base and / or inorganic base; The solvent is selected from any one or more of water, ethanol or ethyl acetate; The template agent is selected from any one or more of tetrapropylammonium hydroxide, n-butylamine or tetrapropylammonium bromide.

3. The preparation method according to claim 1 or 2, characterized in that: Calculated based on SiO2 in the silicon source and Al2O3 in the aluminum source, the molar ratio of the silicon source, aluminum source, template, solvent, and alkaline substance is 1:(0.0332~0.1):(0.1~0.5):(12~30):(0.05~0.15).

4. The preparation method according to any one of claims 1 to 3, characterized in that The crystallization temperature is 120-180°C and the time is 10-72 h; The temperatures of the first calcination and the second calcination are independently 450-700° C., and the times are independently 3-6 h.

5. The preparation method according to any one of claims 1 to 4, characterized in that The reagent for the ion exchange is an acidic solution; The acidic solution includes 0.1-1 mol / L hydrochloric acid solution; The molar ratio of the product after the first calcination to the acidic solution is 1:(2-5).

6. The preparation method according to any one of claims 1 to 5, characterized in that The temperature of the ion exchange is 60-80°C and the time is 2-4 h.

7. The ZSM-5 molecular sieve with surface defects prepared by the preparation method according to any one of claims 1 to 6.

8. A catalyst for catalytic cracking, characterized in that: By weight, it comprises 20-40 parts of kaolin; 30-50 parts of active components; and 10-30 parts of binder; The active component is a surface-defective ZSM-5 molecular sieve prepared by the preparation method according to any one of claims 1 to 6.

9. The catalyst according to claim 8, characterized in that The binder is selected from any one or more of alumina sol, silica sol, acidified pseudo-boehmite, water glass or aluminum phosphate.

10. The catalyst according to claim 8 or 9, characterized in that The raw material for catalytic cracking is selected from any one or more of C5-C8 alkanes, C5-C8 olefins or C6-C8 aromatics.